Design and Development of EMG Monitoring Based Human-Machine Interface Using Nextion Display - Zakaria, Uswatun Khasanah; Jumadi, Nur Anida (Evolution in Electrical and Electronic Engineering, 2026)
Many rehabilitation devices use button-based interface that limit real-time feedback, accessibility and user interaction, reducing compliance and effectiveness in home-based monitoring. This project develops a user-friendly Human-Machine Interface (HMI) to replace buttons, creates a communication algorithm between a Nextion HMI display and microcontroller, and evaluates real-time system response. Methodology included hardware development using EMG sensor, a 3D-printed casing using Fusion 360, Canva-designed for GUI layouts, and UART implementation. EMG testing assessed the developed system under three muscle contraction with load. Average maximum amplitudes were 0.80 mV, 1.55 mV, and 2.68 mV respectively, confirming increased muscle activity. Higher EMG amplitudes appeared in overweight subjects, but underweight subjects also showed increased activity under load, indicating physiological variation beyond BMI affects activation. Results validate that the EMG system reliably records muscle activation patterns in real-time via web interface. While full real-time visualization was not implemented, the GUI integration shows future potential. This research confirms the HMI-based EMG monitoring system is user-friendly for smart rehabilitation. Future work will target full real-time integration, muscle fatigue analysis, and improved home-based usability.